Demokratyczne relacje nauczyciela z dzieckiem w przedszkolu = Democratic teacher-child relations in kindergartens - Olczak, Agnieszka (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
The author discusses the relationships that the teacher builds with a preschool child. She shows the complexity of the problem and the relationship between the quality of the relations with the way the child is perceived by the teacher and the adult`s concept of the child.
Keywords: dziecko; przedszkole; demokratyczne relacje; wychowanie; child; kindergarten; democratic relations; education